Tigridiopalma longmenensis (Melastomataceae), a new species from Guangdong, China - Wang, Hui-Feng; Wang, Zheng-Feng; Qin, Qiao-Mei; Cao, Hong-Lin; Guo, Xiao-Ming (Phytotaxa, 2021)
Tigridiopalma longmenensis, a new species from Guangdong, China, is described. This species differs from its ally, T. magnifica, by the polychasium consisting of scorpioid cymes, hypanthium with carinas on angles, and longer stamens with a conspicuously white or pink spur at the connective base of anther. A diagnosis and a distribution map of the two species are also provided. The complete chloroplast genome of T. longmenensis was reported here. Phylogenetic analyses based on complete chloroplast genomes from T. longmenensis and other 15 Melastomataceae species indicated that T. longmenensis is sister to T. magnifica. The discovery of T. longmenensis terminates Tigridiopalma as a monotypic genus.